ئامادەكردنى پێوەرێك دەربارەى زيرەكى ژينگەيى بۆ خوێندكارانى پۆلى هەشتەمى بنەڕەتى لە كوردستان - حسین, پ.د جواد نعمت; سعید, پ.ى.د. فۆاد خالد; صابر, کانیاو کمال (Sulaimani Journal for Humanities, 2023)
The research aimed to prepare a test on natural environmental intelligence for students of the eighth grade of primary school in the Kurdistan Region, in the context of the geographical material prescribed for that grade, and the descriptive approach was adopted to complete the research according to the nature of its subject and goal, and the research sample consisted of exam preparation procedures such as "stability", from (70 students) were randomly selected from the students of the School in the city of sulaimanyah, which was intentionally selected for the purpose of research, and in the final result, a special test was prepared for natural environmental intelligence, consisting of (20) A mock paragraph of the type of multiple choice, after securing all the conditions and psychometric standards specified for such a test, such as: honesty, stability, coefficient of ease, difficulty and discrimination of the paragraphs, as well as the key to the correct answers, and the standard of intelligence levels of the test.